Contraceptive efficacy of recombinant porcine zona proteins and fusion protein encompassing canine ZP3 fragment and GnRH in female beagle dogs. (15th March 2022) - Gupta, Satish K.; Toor, Sagarika; Minhas, Vidisha; Chaudhary, Piyush; Raman, Muthusamy; Anoop, S.; Panda, Amulya K.
Abstract: Problem: To manage population of dogs ( Canis familiaris ), the efficacy of recombinant proteins‐based contraceptive vaccines to inhibit fertility has been evaluated in female beagle dogs. Method of study: Female beagle dogs ( n  = 4) were immunized with physical mixture of Escherichia coli ‐expressed recombinant porcine ZP3 with promiscuous T cell epitope of tetanus toxoid (TT‐KK‐pZP3) and porcine ZP4 with promiscuous T cell epitope of bovine RNase (bRNase‐KK‐pZP4), or with a fusion protein encompassing dog ZP3 fragment and two copies of GnRH with appropriate promiscuous T cell epitopes (dZP3‐GnRH2 ); control animals received only alum, the adjuvant. The immunized animals were followed‐up for antibody titres by ELISA as well as for fertility status subsequent to mating with male dogs. Results: Active immunization of female dogs following a three injections schedule at 4‐week intervals with a physical mixture of TT‐KK‐pZP3 + bRNase‐KK‐pZP4 as well as dZP3‐GnRH2, led to generation of significant antibody titres against respective recombinant proteins. Active immunization with dZP3‐GnRH2 also led to generation of antibodies reactive with both dZP3 and GnRH. A booster dose on day 383 led to an increase in antibody titres and circulating antibodies against respective recombinant proteins could be observed on day 528. Antibodies in immune serum samples from dogs immunized with TT‐KK‐pZP3 + bRNase‐KK‐pZP4 or dZP3‐GnRH2 reacted with native canine ZP as assessed by an indirect immunofluorescence assay. Mating studies revealed a reduced number of pregnancies as well as a significant reduction in the number of pups born in the female dogs immunized with dZP3‐GnRH2 as compared to the adjuvanted control. Curtailment of pregnancy in dZP3‐GnRH2 immunized group was associated with antibody titres against dZP3‐GnRH2 . However, immunization with recombinant TT‐KK‐pZP3 + bRNase‐KK‐pZP4 did not significantly decrease the number of pups born as compared to the adjuvanted control. Conclusion: These studies revealed the potential of recombinant dZP3‐GnRH2 ‐based contraceptive vaccine to curtail fertility in female dogs. Large scale studies to establish the efficacy and safety of this recombinant protein for the management of community dog population are thus warranted.